2022
DOI: 10.3390/jcm11020461
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Evaluation of the Right Heart-Pulmonary Circulation Unit in Patients Candidate to Transjugular Intrahepatic Portosystemic Shunt

Abstract: In Europe, liver cirrhosis represents the fourth-most common cause of death, being responsible for 170,000 deaths and 5500 liver transplantations per year. The main driver of its decompensation is portal hypertension, whose progression radically changes the prognosis of affected patients. Transjugular intrahepatic portosystemic shunt (TIPS) is one of the main therapeutic strategies for these patients as it reverts portal hypertension, thus improving survival. However, the coexistence of portal hypertension and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In the current paper, the patient had absolute contraindications for TIPS [18]. BRTO was not discussed due to a lack of expertise.…”
Section: Discussionmentioning
confidence: 99%
“…In the current paper, the patient had absolute contraindications for TIPS [18]. BRTO was not discussed due to a lack of expertise.…”
Section: Discussionmentioning
confidence: 99%
“…11,63 The recent rise in cases with nonalcoholic fatty liver disease (NAFLD) needing TIPS makes the issue of cardiac decompensation even more relevant, as these patients commonly have multiple associated comorbidities such as obesity, diabetes, hypertension, high cholesterol, and high incidence of renal and cardiac disease. 64 Studies have found a close correlation between the RAP and portal pressures > 25 mm Hg before TIPS with developing symptomatic heart failure after the procedure. 65,66 Other risk factors include the presence of previous congestive heart failure, preexisting cirrhotic cardiomyopathy (CCM), prolonged QTc interval, left atrial dilatation, an elevated pre-TIPS BNP > 40 pg/mL, and the presence of severe aortic stenosis.…”
Section: Renal Function Complicationsmentioning
confidence: 96%
“…11 63 The recent rise in cases with nonalcoholic fatty liver disease (NAFLD) needing TIPS makes the issue of cardiac decompensation even more relevant, as these patients commonly have multiple associated comorbidities such as obesity, diabetes, hypertension, high cholesterol, and high incidence of renal and cardiac disease. 64…”
Section: Postprocedural Complicationsmentioning
confidence: 99%